2016
DOI: 10.1007/s11240-016-0969-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a grape bZIP transcription factor, VqbZIP39, in transgenic Arabidopsis thaliana confers tolerance of multiple abiotic stresses

Abstract: The basic region/leucine zipper (bZIP) transcription factors are known to play key roles in response to abiotic stress. In this study, a bZIP gene (VqbZIP39) was isolated from grape (Vitis quinquangularis) and constitutively expressed in Arabidopsis under control of the cauliflower mosaic virus 35S promoter. The transgenic Arabidopsis thaliana plants showed enhance salt and drought stress tolerance during seed germination and in the seedling and mature plant stages. Various physiological parameters related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…Plants utilize both enzymatic and nonenzymatic mechanisms for scavenging ROS (Cheng et al, 2016;Shigeoka et al, 2002;Wang et al, 2015a;Zhou et al, 2013). For example, under drought treatment, overexpression of VqbZIP39 in Arabidopsis increases the activities of CAT, POD and SOD (Tu et al, 2016). Overexpression of MdcyMDH also enhances SOD and CAT activities in transgenic apple callus and in transformed tomato plants (Yao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Plants utilize both enzymatic and nonenzymatic mechanisms for scavenging ROS (Cheng et al, 2016;Shigeoka et al, 2002;Wang et al, 2015a;Zhou et al, 2013). For example, under drought treatment, overexpression of VqbZIP39 in Arabidopsis increases the activities of CAT, POD and SOD (Tu et al, 2016). Overexpression of MdcyMDH also enhances SOD and CAT activities in transgenic apple callus and in transformed tomato plants (Yao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1). A phylogenetic analysis indicated that VlbZIP30 is most closely related to the group A ABF/DPBF TFs, which have previously been shown to be involved in ABA and drought stress signaling in A. thaliana (Kang et al , 2002; Kim et al , 2002; Fujita et al , 2005; Yoshida et al , 2015), and in grapevine (Nicolas et al , 2014; Tu et al , 2016a) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, ABF2/bZIP39 (VIT_18s0001g10450), which was characterized as being involved in ABA signaling in grapevine cell culture, has been reported to transiently trans-activate the expression of NAC17 (VIT_19s0014g03290) and PUB19 (VIT 17s0000g08080) following ABA treatment (Nicolas et al , 2014; Pilati et al , 2017). In addition, overexpression of this gene in A. thaliana enhances tolerance to drought stress through the ABA signaling pathway (Tu et al , 2016a), suggesting that NAC17 and PUB19 may enhance drought stress in grapevine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations